Common Virtualized Environment in Telematics Labs - Fernández, F. J.; Sierra, Antonio J.; Ariza, Teresa; Madinabeitia, Germán; Vozmediano, Juan M. (International Journal of Online and Biomedical Engineering (iJOE), 2013)
The aim of this paper is to show the common scenario for practical content of subjects in the Department of Telematics Engineering by means of virtualization. This Department is responsible for a high number of laboratory groups, requiring many teachers and a high workload. A common environment for all practice groups is desired. A virtual machine was built with the same environment of the Computing Centre at School of Engineering at University of Seville. Then, this virtual machine was provided to students and is used to do practices. This article describes this experience and shows the improvements obtained.